International financial reporting standards and new directions in earnings management - Oliveira, Jonas da Silva; Azevedo, Graça Maria do Carmo; Ferreira, Augusta da Conceicao Santos, 1966- (IGI Global, 2019)
"This book investigates the new directions in earnings management and analyzes its relationship with international financial reporting standards, audits, corporate governance, the public sector, and ethics"--